2020
DOI: 10.3390/cancers12113169
|View full text |Cite
|
Sign up to set email alerts
|

Id1 and PD-1 Combined Blockade Impairs Tumor Growth and Survival of KRAS-mutant Lung Cancer by Stimulating PD-L1 Expression and Tumor Infiltrating CD8+ T Cells

Abstract: The use of PD-1/PD-L1 checkpoint inhibitors in advanced NSCLC is associated with longer survival. However, many patients do not benefit from PD-1/PD-L1 blockade, largely because of immunosuppression. New immunotherapy-based combinations are under investigation in an attempt to improve outcomes. Id1 (inhibitor of differentiation 1) is involved in immunosuppression. In this study, we explored the potential synergistic effect of the combination of Id1 inhibition and pharmacological PD-L1 blockade in three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Studies have also asserted that excess metabolites, such as lactate, alter the environment and affect the functions of immune cells [60,86,87,89,121] . A more comprehensive description of cancer metabolic reprogramming and immune response can be found in other reviews [122][123][124][125] . Collectively, the limited nutrients and redundant metabolites arouse the dysfunction in immune cells, which is one of the leading causes of resistance to ICIs.…”
Section: Glutamine and Tryptophan Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also asserted that excess metabolites, such as lactate, alter the environment and affect the functions of immune cells [60,86,87,89,121] . A more comprehensive description of cancer metabolic reprogramming and immune response can be found in other reviews [122][123][124][125] . Collectively, the limited nutrients and redundant metabolites arouse the dysfunction in immune cells, which is one of the leading causes of resistance to ICIs.…”
Section: Glutamine and Tryptophan Metabolismmentioning
confidence: 99%
“…Therefore, targeting pathways modulating PD-1/-L1 expression might show potential for overcoming the resistance to ICIs, which has been demonstrated in several studies. In the KRAS-mutant lung cancer model, blockade of both PD-1 and helix-loop-helix transcription factor inhibitor of differentiation 1 knock out significantly enhances the amount of CD8 + T cells as well as the expression of PD-L1, which impairs the tumor growth and increases the survival [ 126 ] . In other studies of KRAS mut lung cancer, anti-PD-1 combined with inhibition of the AKT-mTOR pathway by mTOR inhibitor or the STAT3 pathway by natural compound luteolin can remarkably decreased the expression of PD-1 or PD-L1, respectively, which consequently surmounts the resistance to anti-PD-1 [ 127 , 128 ] .…”
Section: Prospective Strategies For Overcoming Resistance To Icismentioning
confidence: 99%
“…In addition, it exerts antitumor immunosuppressive effects by inhibiting dendritic cell differentiation and CD8 + T cell proliferation ( 53 , 54 ). Baraibar et al showed that programmed cell death protein 1 (PD-1) blockade combined with ID1 inhibition increased the infiltration of CD8 + T cells and their programmed death-ligand 1 (PD-L1) expression, thereby significantly enhancing the immunotherapeutic effect ( 55 ). This result explains the lower CD8 + T lymphocyte infiltration in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that TP53 or KRAS mutant NSCLC patients, especially those with co-occurring TP53/KRAS mutations, showed remarkable clinical benefit to anti-PD-1 inhibitors by some literatures, [11–13] patients with co-occurring SMARCA4/KRAS mutations were presented with extremely poor prognosis. In that retrospective research, the deleterious effect on immunotherapy outcomes in SMARCA4-deficient/KRAS-mutant NSCLC was showed as a lower ORR (22% vs 0%, P = .03), a significantly shorter mPFS (4.1 vs 1.4 months, HR = 0.25 [95% CI: 0.14–0.42], P < .001), and a significantly shorter median overall survival (15.1 vs 3.0 months, HR = 0.29 [95% CI: 0.17–0.50], P < .001) compared with SMARCA4-wt KRAS-mutant NSCLCs.…”
Section: Introductionmentioning
confidence: 99%